2015
DOI: 10.1016/j.actbio.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-functionalized silk materials for enhancing adipogenic differentiation of bone marrow-derived human mesenchymal stem cells

Abstract: Curcumin, a natural phenolic compound derived from the plant Curcuma longa, was physically entrapped and stabilized in silk hydrogel films and its influence on human bone marrow-derived mesenchymal stem cells (hBMSCs) was assessed related to adipogenic differentiation. The presence of curcumin significantly reduced silk gelation time and changed the porous morphology of gel matrix, but did not change the formation of silk beta-sheet structure. Based on spectrofluorimetric analysis, curcumin likely interacted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 34 publications
2
32
0
Order By: Relevance
“…3740 Silk materials used in these studies were mainly air-dried films. Drying process usually takes a few hours to overnight depending on the film thickness and time/temperature used.…”
Section: Discussionmentioning
confidence: 99%
“…3740 Silk materials used in these studies were mainly air-dried films. Drying process usually takes a few hours to overnight depending on the film thickness and time/temperature used.…”
Section: Discussionmentioning
confidence: 99%
“…The release rate was enhanced by the addition of surfactant to increase the solubility of hydrophobic molecules. On previous work, Li et al (2015) also reported that the release of curcumin from silk hydrogel films was significantly enhanced when the release assay was performed in PBS with Tween80 and methanol supplement compared to that of PBS without supplement [38]. The pH of the solution was found to have had a minor effect on the dissolution of curcumin, but the addition of surfactants to the solution was observed to significantly increase the molecule's solubility.…”
Section: Release Assaymentioning
confidence: 99%
“…In particular, it has been suggested that curcumin might concentrate at the material surface or in the cell membrane in contact with the material rather than being released into the medium. 45 …”
mentioning
confidence: 99%